Clopidogrel transfer into human milk: case series – a contribution from the ConcePTION project - Van Neste, Martje; Nauwelaerts, Nina; Mols, Raf; Krutsch, Kaytlin; Ceulemans, Michael; Passier, Anneke; Smits, Anne; Annaert, Pieter; Allegaert, Karel (Frontiers in Pharmacology, 2025)
IntroductionImplementation of breastfeeding recommendations is hampered by–among others–lacking information regarding medicine safety during breastfeeding. This article describes the clinical and pharmacokinetic data of breastfeeding mothers using clopidogrel (CLP) as secondary prevention following (suspicion of) a cerebrovascular accident.MethodsA 29-year-old and 42-year-old woman were chronically treated with 75 mg CLP once daily. Human milk samples were collected at 7 and 9 months (patient 1), and at 14 months postpartum (patient 2). Each sampling period, two maternal blood samples as well as one infant blood sample were collected. Concentrations of CLP, clopidogrel carboxylic acid (CCA) and clopidogrel active metabolite (CAM) derivatized were analyzed using liquid chromatography with tandem mass spectrometry.ResultsThe average steady-state concentration in human milk was 0.96 and 7.40 ng/mL for CLP and CCA, respectively. CAM concentrations in all but two milk samples were below the limit of detection (LOD; 0.004 ng/mL). In the infant plasma sample, CCA level was 0.05 ng/mL but CLP and CAM were undetectable (CLP LOD: 0.003 ng/mL). The mean daily infant dosage (DID) was 82.3, 585.6 and 1.5 ng/kg/day for CLP, CCA and CAM, respectively, and the relative infant dose (RID) for CLP-related exposure remained well below 1%.DiscussionThe estimated infant exposure to CLP and its metabolites via human milk was low in both cases. Although this low exposure was supported by the observed infant plasma concentration, additional studies should confirm CLP safety via human milk, especially considering known variable pharmacokinetics and ontogeny of metabolizing enzymes in infants.